Masticatory myofascial pain syndrome provoked by SARS-COV-2 infection in a patient with orofacial pathology (clinical case) - Lychko, Volodymyr; Lychko, Svitlana; Zhivotovsky, Igor; Burtyka, Mykola (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Myofascial pain syndrome (MFPS) is a chronic pain condition characterised by the appearance of myofascial trigger points (MTP) in muscles. The condition can be caused by various factors and is diagnosed through clinical examination and palpation of MTPs. Recent studies have shown that infections like SARS-CoV-2 can cause MFPS, along with other symptoms. Dentists often encounter the problem of MFPS in patients with temporomandibular joint dysfunction, but it can also develop in patients with a normally functioning joint. Symptoms include pain, sensitivity, and abnormalities in mandible mobility. In this article, the case of MFPS in a person with orofacial pathology after SARS-CoV-2 diagnosis is presented. Materials and methods of research. Describes a person who has the instability of the bite caused by the absence, destruction and disposition of the chewing teeth led to disorders of the chewing muscles. The patient was found to have appearing MFPS symptoms after COVID-19. The systematic online search of articles utilising the search terms «Coronavirus, SARS-COV-2 and Myofascial pain syndrome», published between January 2020 and October 2023, was performed. Results. The patient was diagnosed with SARS-CoV-2 in October 2021 and was hospitalised for 10 days. After discharge, she went to the dentist with complaints of headache and stiffness in the area of masticatory muscles, absence and destruction of lateral teeth, difficulty in chewing food, mobility and displacement of individual teeth, periodic bleeding gums, as well as aesthetic disorders. During the objective examination, secondary partial adentia was revealed, which led to instability of the bite, defects of the hard tissues of the chewing teeth, pathological wear of the frontal group, and traumatic occlusion phenomena. During palpation, trigger points were found in the area of the masticatory and temporal muscles. The patient underwent a series of ten trigger point injections (dry needling) in her chewing muscles, with about 30 % immediate relief. Conclusion. MFPS can be caused by various factors, including infections like SARS-CoV-2. The diagnosis is based on clinical examination and palpation of MTPs, and treatment may include trigger point injections, physical therapy, and non-invasive therapy methods. In the presented case, the patient had partial adentia, leading to instability of the bite and MFPS symptoms after SARS-CoV-2 diagnosis. Prompt diagnosis and management of MFPS are necessary to improve the patient’s quality of life.